THE RELATIONSHIP BETWEEN GOVERNMENT BODIES AND CIVIL SOCIETY INSTITUTIONS TO PROMOTE INTEGRITY (Journal of actual problems of jurisprudence, 2024)
This work is devoted to the study of the relationship between government agencies and civil society institutions in the context of the formation of integrity in the Republic of Kazakhstan. In modern society, achieving and maintaining integrity is one of the key tasks of the state, which is aimed at maintaining law and order, economic development and ensuring the well-being of citizens. This study analyzes the role and functions of government bodies and civil society institutions in the formation of integrity in the Republic of Kazakhstan. Government bodies play a key role in maintaining law and order, adopting and implementing legislative acts, and monitoring their implementation. They are also responsible for maintaining public safety, fighting corruption and crime, and creating conditions for economic development and social well-being. However, the role of government agencies is often limited and is not always able to effectively solve all problems. Therefore, there is a need for the active participation of civil society institutions. Civil society institutions, such as non-governmental organizations, public associations, trade unions, media and others, play an important role in monitoring power, ensuring civic participation and shaping public opinion. The main goal of this study is to analyze the relationship between government agencies and civil society institutions in the context of building integrity in the Republic of Kazakhstan. The study assessed the effectiveness of interaction between these structures, their interaction and mutual dependence on each other. This research was prepared as part of the implementation of the scientific project of grant funding IRN AP14871865 “Political and legal problems of the formation of integrity in the Republic of Kazakhstan in the modern period.” Key words: government bodies, anti-corruption, transparency, civil society institutions, public control, integrity.